The Macroeconomic Imbalance Procedure at the Heart of EU Economic Governance Reform - Willi Koll; Andrew Watt (Intereconomics)
Abstract While the euro officially came into being in 1999, it was the introduction of euro notes and coins 20 years ago in January 2002 that made the common currency a tangible reality for European citizens. The circle of member states has since grown from 11 to 19, and a growing section of the population no longer has any personal experience with a “national” currency, yet the debate on the legal and institutional framework underpinning the common currency has never gone away.